Study of the oviposition response of black soldier fly (BSF)in the presence of banana and pupal remains - Tan, Pei Chin; Sim, Siong Fong (2020)
Black soldier fly (BSF), Hermetia illucens, is an important beneficial insect.Numerous studies have been conducted to understand the oviposition behavior and preferences of BSF. This paper reports the effects of decomposition level of food and presence of pupal remnants on the oviposition responses of BSF. Cages comprising of four oviposition sites, housed with five male and female BSF were prepared. Gravid females were provided with equal opportunities to oviposit in two sites with ripened banana (mildly ripened (MR)or over-ripenedbanana(AR)) and two other sites with fresh banana (OV). Three replicates in clockwise replication design were set up. The presence of pupal cases inhigh, mediumand low abundance were studied. The number of eggs deposited at different sites were counted and expressed in percentageand oviposition attraction index (OAI). Gravid BSF females showed greater attraction to sites with over-ripened banana likely associating with the odor. BSF females also exhibited a preference for egg laying at sites with less pupae cases.Sites with the most abundance pupae cases were far less enticing as the pupae cases may deter the ovipositing BSF. The findings of this study is important for development of effective egg trapping and collection strategies in BSF farming.